Optimal Experience and Personal Growth: Flow and the Consolidation of Place Identity - Bonaiuto, Marino; Mao, Yanhui; Roberts, Scott; Psalti, Anastasia; Ariccio, Silvia; Ganucci Cancellieri, Uberta; Csikszentmihalyi, Mihaly (Frontiers in Psychology, 2016)
This study examined the relationship between flow experience and place identity, based on eudaimonistic identity theory (EIT) which prioritizes self-defining activities as important for an individual’s identification of his/her goals, values, beliefs, and interests corresponding to one’s own identity development or enhancement. This study focuses on place identity, the identity’s features relating to a person’s relation with her/his place. The study is also based on flow theory, according to which some salient features of an activity experience are important for happiness and well-being. Questionnaire surveys on Italian and Greek residents focused on their perceived flow and place identity in relation to their own specific local place experiences. The overall findings revealed that flow experience occurring in one’s own preferred place is widely reported as resulting from a range of self-defining activities, irrespective of gender or age, and it is positively and significantly associated with one’s own place identity. Such findings provide the first quantitative evidence about the link between flow experienced during meaningfully located self-defining activities and identity experienced at the place level, similarly to the corresponding personal and social levels that had been previously already empirically tested. Results are also discussed in terms of their implications for EIT’s understanding and enrichment, especially by its generalization from the traditional, personal identity level up to that of place identity. More generally, this study has implications for maintaining or enhancing one’s own place identity, and therefore people–place relations, by means of facilitating a person’s flow experience within psychologically meaningful places.